Insight into the influence of particle sizes on characteristics and microbial community in the anammox granular sludge. (February 2021) - Chen, Chongjun; Jiang, Ying; Zou, Xinyi; Guo, Menglei; Liu, He; Cui, Minhua; Zhang, Tian C.
Graphical abstract: Highlights: Different physicochemical characteristics on anammox granular sludge with different particle sizes. The removal efficiency of ammonium and nitrite as well as the specific anammox activity increased with an increase in particle size. The granular sludge with a particle size of 1.0 − 1.5 mm had the largest biomass and relative abundance values of anammox bacteria. Abstract: Currently, little information is available on how the particle size would influence the physicochemical characteristics, nitrogen conversion activity and microbial community in the anammox sludge granules. This study was targeting to answer the question by studying anammox granular sludge with average particle sizes ranging from 0.5 − 1.0, 1.0 − 1.5, 1.5 − 2.0 and > 2.0 mm. Results indicated that the wet density and settling velocity were positively correlated with particle size. However, the volatile suspended sludge/suspended sludge (VSS/SS) ratio and particle integrity coefficient (IC) decreased with an increase in particle size. The granular sludge with a particle size of 1.0 − 1.5 mm had the largest extracellular polymeric substances (EPS) content and protein/polysaccharide (PN/PS) ratio. The removal efficiency of ammonium and nitrite as well as the specific anammox activity (SAA) increased with an increase in particle size. High-throughput sequencing showed that the richness and diversity of the microbial community decreased firstly and then increased with an increase in particle size. The granular sludge with a particle size of 1.0 − 1.5 mm had the lowest diversity, but that of 0.5 − 1.0 mm had the largest biomass and relative abundance values of anammox bacteria. The granular sludge size should be controlled below 1.5 mm to maintain the predominant microorganisms of anammox bacteria, while particle sizes of 1.5 − 2.0 mm should be selected to maintain high nitrogen removal performance.